Phenotype Heterogeneity and the Association Between Visual Acuity and Outer Retinal Structure in a Cohort of Chinese X-Linked Juvenile Retinoschisis Patients - Guo, Qingge; Li, Ya; Li, Jiarui; You, Ya; Liu, Changgeng; Chen, Kang; Li, Shuyin; Lei, Bo (Frontiers in Genetics, 2022)
Purpose: X-linked juvenile retinoschisis (XLRS), caused by mutations in the RS1 gene, is an X-linked recessive inherited disease that typically involves both eyes in the first two decades of life. Recently, phenotype heterogeneity of this condition has drawn increasing attention. We reported various phenotypes caused by RS1 gene mutations in eleven patients from ten Chinese families. Methods: Data on the medical history of the patients from ten Han families of central China were collected. Ophthalmic examinations including the best-corrected visual acuity (BCVA), fundus photography, ultra-wide angel sweep source optical coherence tomography (SS-OCT), electroretinography (ERG) were performed. Adaptive optics (AO) images were acquired to evaluate the cone photoreceptor mosaic when applicable. Venous blood of the probands and their family members was collected, and DNA was subjected to sequencing based on next-generation sequencing with a custom designed targeted gene panel PS400 for inherited retinal diseases. Validation was performed by Sanger sequencing and cosegregation. Pathogenicity was determined in accordance with the ACMG guidelines. Results: Ten RS1 mutations including 8 missense mutations and 2 terminator mutations were identified in 10 XLRS families. c.657C>A (p.C219X) was a novel mutation in this cohort. These patients showed a variety of clinical phenotypes including fovea schisis, bullous retinoschisis, macular or peripheral atrophy. Fifteen eyes of eight patients exhibited macular retinoschisis, and twelve eyes of seven patients exhibited peripheral retinoschisis. In addition, three patients showed asymmetrical fundus manifestations.Of importance, three patients without macular retinoschisis were misdiagnosed until genetic testing results were obtained. AO showed decrease of cone density and loss of regularity in the cystic schisis macular of XLRS. Furthermore, the BCVA was associated with the photoreceptor inner segment and outer segment (IS/OS) thickness. Conclusion: With complicated clinical manifestations, a considerable portion of XLRS patients may present various phenotypes. It should be noticed that asymmetry fundus appearance in both eyes could lead to misdiagnosis easily. Thus, genetic testing is crucial for making a final diagnosis in those patients who were suspected with amblyopia, bilaterally or unilaterally macular atrophy, or conditions presenting asymmetric fundus appearance. In addition, residual cone photoreceptor structure was critical for the maintenance of useful vision.